Bandura's social cognitive theory (SCT) in a cross-nation study of software piracy. - Matthews, M. S. (My University, 2009)
This quantitative study is designed to examine possible cross-national differences between a Zambian and a South Africa student sample on specific aspects of Bandura’s Social Cognitive Theory in relation to software piracy. Software piracy is when people make copies of the computer software without permission or they load software onto more machines than the licensed agreement says they can. A questionnaire composed of previously developed scales measuring attitudes, social norms, piracy intentions, incentives, deterrents, self-efficacy and moral disengagement within the context of software piracy was collated. During economics classes in a major University in Zambia and one in South Africa 150 copies of the questionnaire were handed out. The South African sample consisted of 37 males and 34 females all aged between 18-28, 44 were in 2nd year and 27 were in 3rd year. The Zambian sample consisted of 57 males and 12 females, 53 were between 18-28, 12 between 29-38 and 4 between 39-49, 27 were in their 3rd years of study and 42 in 4th year. The scales had adequate reliabilities (.60 to .89). There was sufficient evidence to suggest that there is a statistical difference between the two countries on attitudes and social norms. The South African sample had more positive attitudes and more favourable social norms than Zambia. South Africa reported higher extrinsic motivators (monetary, reinforcement and reciprocal exchange, and self-evaluative and reciprocal exchange) and Zambia reported higher intrinsic motivators and being deterred by the threat of harsh punishments. There was also sufficient evidence to suggest that attitudes, social norms and self-efficacy predict (in order of best predictors) piracy intention in both samples. Moral disengagement did not act as a moderator or mediator between attitudes, social norms and self-efficacy and piracy intention in either sample. Theoretical and practical implications are discussed.
Keywords: Social cognitive theory; Software piracy